Association between smoking and outcomes in older adults with atrial fibrillation - Pawar, Pushkar P. (2011)
Tobacco smoking is a risk factor for atrial fibrillation (AF), but little is known about the impact of smoking in patients with AF. Of the 4060 patients with recurrent AF in the Atrial Fibrillation Follow-up Investigation of Rhythm Management (AFFIRM) trial, 496 (12%) reported having smoked during the past two years. Propensity scores for smoking were estimated for each of the 4060 patients using a multivariable logistic regression model and were used to assemble a matched cohort of 487 pairs of smokers and nonsmokers, who were balanced on 46 baseline characteristics. Cox and logistic regression models were used to estimate the associations of smoking with all-cause mortality and all-cause hospitalization, respectively, during over 5 years of follow-up. Matched participants had a mean age of 70 ± 9 years (± S.D.), 39% were women, and 11% were non-white. All-cause mortality occurred in 21% and 16% of matched smokers and nonsmokers, respectively (when smokers were compared with nonsmokers, hazard ratio = HR = 1.35; 95% confidence interval = 95% CI = 1.01–1.81; p = 0.046). Unadjusted, multivariable-adjusted and propensity-adjusted HR (95% CI) for all-cause mortality associated with smoking in the pre-match cohort were: 1.40 (1.13–1.72; p = 0.002), 1.45 (1.16–1.81; p = 0.001), and 1.39 (1.12–1.74; p = 0.003), respectively. Smoking had no association with all-cause hospitalization (when smokers were compared with nonsmokers, odds ratio = OR = 1.21; 95% CI = 0.94–1.57, p = 0.146). Among patients with AF, a recent history of smoking was associated with an increased risk of all-cause mortality, but had no association with all-cause hospitalization.